NPC1L1 rs217434 A > G as a Novel Single Nucleotide Polymorphism Related to Dyslipidemia in a Korean Population - Cho, Dahyun; Huang, Ximei; Han, Youngmin; Kim, Minjoo (Biochemical genetics, 2024)
A relationship between cholesterol levels and Niemann-Pick C1-Like 1 ( NPC1L1 ) polymorphisms in diverse populations was found in previous studies. However, relevant research on this association in the Korean population is relatively scarce. Therefore, the current study sought to examine the correlation between the NPC1L1 rs217434 A > G polymorphism and clinical as well as biochemical variables pertaining to dyslipidemia in the Korean population. This cross-sectional single-center study included 1404 Korean subjects aged 20–86 years, grouped based on dyslipidemia presence (normal and dyslipidemia) and genotype (AA or AG). After adjusting for sex and age, it was discovered that the dyslipidemia group’s BMI, diastolic blood pressure, glucose-related indicators, lipid profile, high-sensitivity C-reactive protein (hs-CRP), and parameters of oxidative stress were considerably different from the normal group’s values. When grouped according to genotype, individuals in the AG group exhibited greater total cholesterol, low-density lipoprotein cholesterol, hs-CRP, and 8-epi-prostaglandin F 2α in comparison to those in the AA group. Moreover, individuals with dyslipidemia and the AG genotype exhibited unfavorable outcomes for lipid profiles, markers related to glucose and inflammation, and markers of oxidative stress. This study provided evidence for a relationship between the NPC1L1 rs217434 A > G genotype and dyslipidemia in the Korean population, which highlights the potential of the NPC1L1 rs217434 A > G genotype as an early predictor of dyslipidemia.